Mechatronics : principles, concepts and applications - Mahalik, N. P. (Nitaigour Premchand) (McGraw-Hill, 2004)
This book is designed for the first undergraduate course in mechatronics. It details the basic principles of analysis, design and control of modern mechatronic systems. Key features: latest technological developements microprocesssor and microcontroller-based control systems soft computing technology for intelligent and feedback control scheme and diagnostics methodologies component-based system design case studies on autonomous guided vehicle [agv] conveyor-based material handling systems high speed spindle systems useful tips, tricks, judgement adn heuristics relative merits and demerits of differnt techniques explained.